PENYULUHAN TENTANG PENGARUH PEMBERIAN HANDSAPLAS EKSTRAK RHIZOM JAHE MERAH DAN DAUN SALAM SEBAGAI RHEMATOID ARTHERITIS PADA PASIEN DI PUSKESMAS TALUN KENAS - bunga rimta barus (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Rheumatoid arthritis is the most common arthritis in the elderly, caused by autoimmune processes and often recurring. The purpose of the study was to analyze the risk factors for recurrence of rheumatoid arthritis in elderly people aged 40 to 65 years. This survey design uses quantitative descriptions. The respondents of this study were selected from 150 respondents using purposive sampling technique based on elderly patients with RA. The variables were examined using questionnaires developed by the researchers themselves and tested for validity and reliability. From the results of the study it is known that there are three factors associated with rheumatoid arthritis patients are age factors, lifestyle factors and dietary factors. This is also due to the fact that there are more women than men. The conclusion of this study is that the risk factors for recurrence of rheumatoid arthritis in the elderly are activity, lifestyle and eating habits. Therefore, the activity factor is the most powerful factor of influence and many respondents stated that heavy work or activity is often done repeatedly. Suggestions for further research can explore additional factors that can aggravate RA recurrence, and respondents should be able to reduce excessive activity to avoid recurrence.